Dinâmica espaço-temporal na disseminação da COVID-19 em Curitiba - Oliveira, Alcides Augusto Souto de (2023)
Since it was considered a Public Health Emergency of international concern, COVID- 19 has been affecting millions of people and has overloaded health systems, negatively reflecting on people’s health and lifestyle, in addition to destabilizing the economy on all continents. The world witnessed the rapid spread of confirmed cases of Sars-CoV-2 and in the first months of the pandemic, it was observed that large cities, in different parts of the world, became privileged stages of contagion and spread with an explosive growth of the disease. Therefore, the city emerged as an essential scale of analysis in understanding the spread of COVID-19. The present research is an analytical study having as a source of information data available in the National Information System tabulated by the Municipal Health Department of Curitiba whose objective was to present the profile of the sócio-spatial evolution of the COVID-19 pandemic in Curitiba, as well as the historical record of coping measures adopted by the municipal administration. Despite the fact that the virus spread quickly to all the city’s neighborhoods, it was found that the spread took place from the most central regions of the city to those more peripheral and with lower household income, thus highlighting the need to implement sanitary, managerial and socioeconomic measures that included, in particular, the reorganization of the public health system and the removal and monitoring of sick people in order to reduce the risk of collapse of services and guarantee the health of the population, especially the most vulnerable people.